(untitled) (Bangladesh Medical Journal Khulna, 2014)
Human papilloma virus is an oncogenic DNA virus, which is identified in 99.7% case of invasive cancer. It is the most prevalent virus involved in sexually transmitted diseases worldwide and an important public health challenge for the prevention of cervical carcinoma. Cervical cancer is the second cause of malignant neoplasia and death in women. The present study was thus designed to detect the risk factors for HPV infection in normal and unhealthy cervix of women attending tertiary care hospital (BSMMU). HPV DNA was detected among the study population using the Hybrid Capture 2 assay, which determined HPV high risk types. A total of 68 women between 25-70 years of age were included in this cross sectional study. Among them 13 (19.1%) cases were tested positive for HPV DNA. The risk factors for HPV infection identified from this result are early sexual activity, lower level of education, early marriage, multi-parity, total duration of sexual activity in years and long term use of oral contraceptive pill and poor socioeconomic condition. Increased awareness and understanding regarding HPV infection would improve the risk of infection and control in sexually active women. HPV diagnosis at early stages of infection is of fundamental importance. The use of HPV test in routine cervical mass screening may not be possible in developing countries like Bangladesh due to its high cost. Nevertheless, it has been shown to be a useful tool when combined with cytology to diagnose high-risk infection in apparently normal tissues, and may help to reduce the risk of cervical cancers. The results obtained from this study ultimately contribute to cervical cancer prevention among Bangladeshi women. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18231 Bang Med J (Khulna) 2013; 46 : 3-6